Efikasnost rada mobilne šumske žičare Konrad Mounty 4000 pri transportu oblog drveta u sastojinama bukve - Danilović Milorad; Antonić Slavica; Stojnić Dušan; Babić Violeta; Gojković Slaven (Glasnik Šumarskog Fakulteta: Univerzitet u Beogradu)
The paper presents the results of research into the efficiency of work of the Konrad Mounty 4000 mobile forest cable yarder with a processor head in the transport of wood assortments in beech stands. The research was conducted through a time and work study. The research was conducted in the Ribnik Forestry and Economic Area, more precisely in the “Ribnik” Forestry Estate. The effects of the operation of the mobile cable yarder differed depending on the operating conditions, the length of the cable route, the lateral distance of attraction, the average volume of the tour, the construction method. The effects of working with a mobile cable yarder with a processor head were determined individually by phase. Norms for cutting and making tree parts depending on the diameter of the tree at chest height. It was found that the speed of movement of the carriage along the mainline, as well as the speed of movement of the load to the mainline decreases with the increase in the volume of the load. The time of pulling the rope and pulling depends on the distance of the pull and the slope of the terrain. With the increase of the transport distance and the average slope of the terrain when pulling the rope uphill, the pulling time increases. Based on the results of the research, it can be concluded that the mobile forest cable car with a harvester head, which was the subject of the research, represents an alternative technical solution when it comes to the first phase of transporting wood assortments in pure beech stands of poor quality.